O cortiço, de Aluísio Azevedo: determinismo e regionalidade - Nobrega, Nára Boninsegna da (My University, 2019)
This thesis aims at analyzing the novel O cortiço, by Brazilian writer Aluísio Azevedo, based on the concepts of Regionality and Determinism. The objective is to relate considerations on racial determinism, environment, history and regionality present in the work. The analysis seeks to establish how the nineteenth century’s deterministic concepts and the regionalities were represented and connected in the plot of the novel. It is known that the author, who was the main representative of the literary school of Naturalism in Brazil, imprinted on his artistic project much of the scientific conceptions in vogue in the last quarter of the nineteenth century. In addition, the novel, published in 1890, represents and was produced during an era of social change in Brazil, in which many important debates occurred, such as the abolition of slavery (which occurred in 1888), equality and the scientific differences between ethnic-racial profiles. It was the age of theories like Determinism, which was developed in Brazil by intellectuals such as Silvio Romero and Nina Rodrigues. The type of slums that named the novel in Portuguese became increasingly common due to the crescent number of freed and fleeing slaves in the late nineteenth century. Such areas also provided housing to people who did not afford to live elsewhere, regardless of the race. They were social spaces formed by miscegenation, something that was heavily debated among scientists regarding the development of the Brazilian population, especially based on racial criteria and scientific thoughts of the nineteenth century. In addition, these urban groupings were the birthplace of modern Brazilian slums, cities and regions; Thus, this work also deals with recent theoretical discussions about region and regionality, since Aluísio Azevedo’s fictional slum, although admittedly seeking to represent all of Brazil, clearly has specific traits of nations, ethnic groups and historical moments – regionalities.
Esta pesquisa busca analisar as representações da regionalidade e do determinismo na obra O cortiço, de Aluísio Azevedo. Procura-se saber quais são os aspectos referentes ao determinismo racial, do meio, do momento histórico e à regionalidade presentes na obra. Assim, tem-se como objetivo analisar como esses determinismos e a(s) regionalidade(s) foram representados e se entrelaçam no romance. Sabe-se que o autor, principal representante da escola literária do Naturalismo no Brasil, imprimiu em seu projeto artístico muito das concepções cientificistas tão em voga quando de sua atuação, no último quartel do século XIX. Além disso, o romance analisado, lançado em 1890, representa e foi produzido durante uma época de efervescência social, em que se discutiam pesadamente, no Brasil, temas como a abolição da escravidão (que ocorrera em 1888), a igualdade ou a diferença entre os perfis étnico-raciais. Foi a época das teorias do determinismo, que tiveram em Silvio Romero e Nina Rodrigues fortes vozes de consonância. Os cortiços foram se tornando cada vez mais comuns, acelerados pelo crescente fluxo de imigrantes, pelo aumento no número de alforrias, pelos negros fugidos, que eram abrigados nessas habitações, além de servirem de moradia para aqueles com baixa renda ou nenhuma. Eram espaços sociais tomados pela miscigenação, objeto de debates entre os intelectuais brasileiros para explicar a formação do povo brasileiro, baseados em critérios raciais e apoiados nas correntes cientificistas do período. Ademais, esses agrupamentos urbanos são a origem das favelas que se desenvolveram nas cidades e regiões brasileiras; por isso, este trabalho também se debruça sobre recentes discussões teóricas a respeito de região e regionalidade, uma vez que o cortiço de Aluísio Azevedo, embora assumidamente tenha buscado representar todo o Brasil, claramente tem traços específicos de nações, etnias e momentos históricos específicos – regionalidades.
Keywords: Azevedo, Aluísio, 1857-1913; Língua portuguesa - Crítica e interpretação; Naturalismo na literatura; Determinismo (Filosofia); Portuguese language - Criticism and interpretation; Naturalism in literature; Determinism (Philosophy)